Social work and human services responsibilities in a time of climate change : country, community and complexity - Howard, Amanda, 1967-; Rawsthorne, Margot; Joseph, Pam; Terare, Mareese; Sampson, Dara; Katrak, Meaghan (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book provides an accessible, research informed text for students, social workers and other social service workers and community development workers focused on practically linking climate change to social justice. It will be required reading for all scholars, students and professionals of social work, social welfare, community development, international development, community health, and environmental and community education"--
Keywords: Social service -- Environmental aspects; Community development; Social justice; Climatic changes; Human ecology; SOCIAL SCIENCE / Human Services; SOCIAL SCIENCE / Third World Development